المقاصد السياسية عند المالكية - أحمد عيسات; د/عبدالرحمن مايدي (جامعة عمار ثليجي الاغواط, 2023)
إن المقاصد السياسية تمثل دائرة جد هامة لما ترتبط من مصالح العباد والبلاد وقد أضحى اليوم ضرورة ملحة يمليها الواقع، وتمليها الإشكاليات والتحديات المعاصرة التي تتجسد على الساحة يوما بعد يوم. وتكتسي آراء الإمام مالك في المقاصد السياسية أهمية خاصة لكونه من حملة آثار الصحابة أفهم الناس لشريعة الله التي شملت كل شيء. ومع أن هناك ظروفا عديدة لم تسمح بتشكل نظرية سياسية مفصلة عند الإمام مالك إلا أنه أمكنتنا الدراسة من استنباط عدد من المقاصد لسياسية الحاسمة من خلال دراسة أقوال الأمام مالك وما نقله عنه تلامذته. وقد قسمنا البحث إلى فصلين تحدثنا في الأول عن المقاصد السياسية عموما وحاولنا حصرها. وتكلمنا في الفصل الثاني عن المقاصد السياسية للإمام مالك مع الحديث على أهمية السياق المكاني والزماني في صياغة هذه المقاصد. وبينا أن هناك مقصدا أساسا هو الرد إلى الله ورسوله تتفرع منه كل المقاصد السياسية الأخرى. الكلمات المفتاحية: الإمام مالك، المقاصد السياسية، نظام الحكم. summary. The political objectives represent a very important circle because they are linked to the interests of the people and the country, and today it has become an urgent necessity dictated by reality, and dictated by the contemporary problems and challenges that are embodied on the scene day after day. Imam Malik's views on political purposes are of particular importance because he is among the bearers of the effects of the Companions, the most understanding people of Allah's law, which included everything. Although there are many circumstances that did not allow the formation of a detailed political theory of Imam Malik, the study enabled us to devise a number of decisive political purposes through studying the sayings of Imam Malik and what his students quoted from him. We have divided the research into two chapters. In the first, we talked about political purposes in general, and we tried to limit them. In the second chapter, we talked about the political purposes of Imam Malik, with a discussion on the importance of the spatial and temporal context in formulating these purposes. And we showed that there is a basic purpose, which is to respond to Allah and His Messenger, from which all other political purposes branch out. Keywords: Imam Malik, political purposes, system of governement